The 7 keys to communicating in Mexico : an intercultural approach - Kelm, Orlando R., 1957-; Roble Hernández Pozas, Olivia del; Victor, David A., 1956- (Georgetown University Press, 2020)
The authors present a practical set of guidelines for people wishing to communicate professionally in Mexico or with Mexicans, following the model of the similar books by Kelm and Victor on Brazil and Japan of presenting on key cultural concepts. Good communication requires more than knowing the language. Olivia Hernandez-Pozas, Orlando Kelm, and David Victor, seasoned cross-cultural trainers for businesspeople, provide a guide through Victor's LESCANT model (Language, Environment, Social Organization, Context, Authority, Nonverbal, and Time). Each chapter addresses one of these topics and demonstrates how to evaluate the differences between Mexico and others in North America, presenting examples to help people avoid common communication mistakes. The book is generously peppered with photographs to provide visual examples. The authors complete the book with a case study chapter on a business interaction between Mexican and other North Americans (NAs). They then gathered comments from various NA professionals working in Mexico and Mexicans working with US professionals about the interactions in the case, providing helpful observations about the situation. The book straddles some language and communication topics, international relations, and reaches into the business community.